2023
DOI: 10.3389/fonc.2023.1203922
|View full text |Cite
|
Sign up to set email alerts
|

Application of DKI and IVIM imaging in evaluating histologic grades and clinical stages of clear cell renal cell carcinoma

QiChao Cheng,
AnLi Ren,
XingHua Xu
et al.

Abstract: PurposeTo evaluate the value of quantitative parameters derived from diffusion kurtosis imaging (DKI) and intravoxel incoherent motion (IVIM) in differentiating histologic grades and clinical stages of clear cell renal cell carcinoma (ccRCC).Materials and methodsA total of 65 patients who were surgically and pathologically diagnosed as ccRCC were recruited in this study. In addition to routine renal magnetic resonance imaging examination, all patients underwent preoperative IVIM and DKI. The corresponding diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…Several studies have demonstrated the clinical utility of three-axis imaging for DKI [ 18 , 38 , 39 ], and Rosenkrantz et al [ 39 ], in a review, summarized that three-axis imaging is sufficient for several imaging directions. As for imaging with a lower maximum b-value, several clinical studies have also shown the clinical utility of DKI with a lower maximum b-value [ 14 , 19 , 20 , 40 , 41 ] for clear cell renal cell carcinoma, head and neck cysts and tumors, rectal cancer, and prostate cancer. Clinical studies using a maximum b-value of 800 s/mm 2 for SDI have also shown that DKI is useful for diagnosing head and neck tumors [ 19 ] and cystic diseases [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have demonstrated the clinical utility of three-axis imaging for DKI [ 18 , 38 , 39 ], and Rosenkrantz et al [ 39 ], in a review, summarized that three-axis imaging is sufficient for several imaging directions. As for imaging with a lower maximum b-value, several clinical studies have also shown the clinical utility of DKI with a lower maximum b-value [ 14 , 19 , 20 , 40 , 41 ] for clear cell renal cell carcinoma, head and neck cysts and tumors, rectal cancer, and prostate cancer. Clinical studies using a maximum b-value of 800 s/mm 2 for SDI have also shown that DKI is useful for diagnosing head and neck tumors [ 19 ] and cystic diseases [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, diffusion kurtosis imaging (DKI), a type of restricted diffusion-weighted (RD) imaging, has garnered attention, and its usefulness in the clinical image-based diagnosis of neurodegenerative diseases, ischemic stroke, and tumors has been reported [ 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 ]. Recently, the combination of intravoxel incoherent motion (IVIM) and amide proton transfer-weighted imaging in addition to DKI has been shown to improve the diagnostic performance by predicting lymph node metastasis in cervical cancer [ 13 ], in distinguishing among histological grades and clinical stages in clear cell renal cell carcinoma [ 14 ], and in predicting molecular subtypes in breast cancer [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%